New progress of glutamine metabolism in the occurrence, development, and treatment of ovarian cancer from mechanism to clinic - Yang, Xiaojing; Li, Zhen; Ren, Hanru; Peng, Xue; Fu, Jie (Frontiers in Oncology, 2022)
Glutamine is a non-essential amino acid that can be synthesized by cells. It plays a vital role in the growth and proliferation of mammalian cells cultured in vitro. In the process of tumor cell proliferation, glutamine not only contributes to protein synthesis but also serves as the primary nitrogen donor for purine and pyrimidine synthesis. Studies have shown that glutamine-addicted tumor cells depend on glutamine for survival and reprogram glutamine utilization through the Krebs cycle. Potential therapeutic approaches for ovarian cancer including blocking the entry of glutamine into the tricarboxylic acid cycle in highly aggressive ovarian cancer cells or inhibiting glutamine synthesis in less aggressive ovarian cancer cells. Glutamine metabolism is associated with poor prognosis of ovarian cancer. Combining platinum-based chemotherapy with inhibition of glutamine metabolic pathways may be a new strategy for treating ovarian cancer, especially drug-resistant ovarian cancer. This article reviews the role of glutamine metabolism in the biological behaviors of ovarian cancer cells, such as proliferation, invasion, and drug resistance. Its potential use as a new target or biomarker for ovarian cancer diagnosis, treatment, and the prognosis is investigated.